Intervensi Lingkungan Toxic pada Kecerdasan Spiritual terhadap Niat Kekerasan Seksual - Novi Tazkiyatun Nihayah; Nur Aksin; Hisny Fajrussalam; Sunan Baedowi (Muttaqien, 2025)
Sexual violence is part of gender-based violence. The Ministry of Women's Empowerment and Child Protection (Ministry of PPPA) of the Republic of Indonesia recorded a 34.8 percent predominance of sexual violence in gender-based violence. This research aims to find out how much the impact of a toxic environment influences spiritual intelligence which leads to intentions to commit sexual violence. This research is classified as quantitative descriptive research with a convenience sampling technique of 77 respondents in Semarang City via an online questionnaire. The analytical tool for this research uses SPSS version 21 through instrument testing, classical assumptions, and regression. The research results showed that spiritual intelligence had a significant negative effect on the intention to commit sexual violence, whereas spiritual intelligence was not affected by the intention to commit sexual violence despite the intervention of a toxic environment. The recommendation of this research is the need for structured efforts to increase spiritual intelligence in the educational sphere through religious deepening, such as the Islamic boarding school system.